Faktor yang mempengaruhi emosi: fokus kepada ibadah haji di Arab Saudi - Zhooriyati Sehu Mohamad,; Intan Hashimah Mohd Hashim,; Zulkarnain Ahmad Hatta, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Emotions are one of the important components that play a vital role in the daily life of man. Emotions play a role in determining the quality of human life, influencing people in decision making, social interactions and behavioral patterns in the environment. Although many studies have been conducted on emotion, studies that study emotions in spiritual contexts are still limited in the field of research. Therefore, this study examines how emotions are influenced by certain factors in the context of pilgrimage. More specifically, this study investigates emotional issues in the context of pilgrimage. To achieve this research objective, a qualitative study using an exploratory approach was conducted in two phases. The first phase of the study involved five participants who completed the selected diary notes for the selected ten days while performing their Hajj worship in Saudi Arabia. The second phase involved 53 participants who completed the open questionnaire for a maximum of six months after returning from performing the pilgrimage. The results of this study were analyzed using thematic analysis. The results show that the emotional experiences during the pilgrimage are varied and are motivated by various factors such as location of worship, activities such as spiritual activities and daily activities, health factors, and social interactions as well as struggles of religiosity and spirituality. The findings of this study detail not only the type of emotion experienced but also the types of factors that may contribute to the development of these emotions. The findings of this study help researchers to better understand the emotional experiences during the pilgrimage.